Chitosan cross-linked poly(aminoanthraquinone)/Prussian blue ternary nitrogen precursor-derived Fe–N–C oxygen reduction catalysts for microbial fuel cells and zinc–air batteries. Issue 18 (29th April 2020) - Zhang, Guoquan; Li, Li; Chen, Mengyao; Yang, Fenglin
Abstract : A chitosan cross-linked poly(1, 5-diaminoanthraquinone)/Prussian blue (PDAA/PB) ternary nitrogen precursor-derived Fe–N–C/800-HT2 catalyst shows highly efficient ORR activity for MFCs and Zn–air batteries. Abstract : Exploiting high-efficiency, cost-effective and robust platinum group metal-free (PGM-free) oxygen reduction reaction (ORR) electrocatalysts is significantly vital for the development of renewable energy storage and conversion technologies. However, the rational design of PGM-free catalysts and accurate control of the well-defined active sites are still the tough challenges. Herein, we report a combined chemical polymerization–spontaneous redox-pyrolysis approach for synthesizing Fe–N–C ORR catalysts, which are derived from the ternary nitrogen precursor chitosan cross-linked poly(1, 5-diaminoanthraquinone)/Prussian blue (PDAA/PB) nanocomposite. After calcination, acid etching and temperature-controlled secondary pyrolysis, the best catalyst Fe–N–C/800-HT2 (secondary pyrolysis temperature of 800 °C) exhibited comparable and even superior ORR activity to the state-of-the-art Pt/C in neutral and alkaline media. In-depth structure-to-property correlation indicated the synergistic effect between the porous graphene-like structure and the finely dispersed Fe–N x active moieties. The well-arranged porous and Fe–N x modulated graphene-like carbon nanostructure is responsible for the prominently enhanced ORR performance. Evaluation of microbial fuel cells (MFCs) and a Zn–air battery assembled with the Fe–N–C/800-HT2 air-cathode showed high open-circuit voltage, high maximum power density, and excellent durability, demonstrating the great potential of the Fe–N–C/800-HT2 catalyst as a substitute for the commercial Pt/C catalyst in energy conversion devices through the rational choice of appropriate precursors and pyrolysis strategy.